2018
DOI: 10.1016/j.cub.2018.10.054
|View full text |Cite
|
Sign up to set email alerts
|

The Muskox Lost a Substantial Part of Its Genetic Diversity on Its Long Road to Greenland

Abstract: Highlights d Successive founder effects caused progressive loss of genetic diversity in the muskox d Evidence of strong population structure in the muskox d Extremely low genetic diversity in the Greenlandic muskox populations d Arctic mammals show striking similarities in their genetic history

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 72 publications
(82 reference statements)
6
51
0
1
Order By: Relevance
“…On Victoria Island, the ongoing decline of muskoxen is concomitant to the apparent emergence or increased occurrence of multiple pathogens and disease syndromes [17][18][19][20]. Given the taxonomic uniqueness of muskoxen, and their limited genetic diversity [21,22], which may influence their resilience to diseases [23], it is important to understand the potential role of infectious diseases in their population dynamics and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…On Victoria Island, the ongoing decline of muskoxen is concomitant to the apparent emergence or increased occurrence of multiple pathogens and disease syndromes [17][18][19][20]. Given the taxonomic uniqueness of muskoxen, and their limited genetic diversity [21,22], which may influence their resilience to diseases [23], it is important to understand the potential role of infectious diseases in their population dynamics and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest negative trends in Arctic sea ice have been observed around Svalbard and the northern Barents Sea (Comiso et al, ; Onarheim et al, ; Stroeve et al, ). Therefore, our study provides an early warning that continued sea ice decline linked to global warming will lead to increased genetic isolation and population differentiation through genetic drift, not only in Svalbard reindeer but also other Arctic wildlife, such as Peary caribou (Jenkins et al, , ; Mallory & Boyce, ), Arctic fox (Geffen et al, ; Norén et al, ), polar bear (Laidre et al, ), and muskox (Hansen et al, ). Indeed, the populations of Svalbard reindeer that were reintroduced into West Spitsbergen are already facing increased demographic isolation due to sea ice loss (Nilsen et al, ; Pedersen et al, ), which increases their vulnerability to current climate change and the increased frequency of extreme winter weather events (Hansen, Aanes, Herfindal, Kohler, & Sæther, ; Peeters et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…This speciation model has been found in recent studies of many organisms (Hartmann et al, 2020;He et al, 2019;Oswald et al, 2017), suggesting that the diverging effects of drift and the homogenizing effects of gene flow were probably in equilibrium, rather than one overwhelming the other. giving us important insights for evaluating the impact of climate change on the extinction potential of a species (Hansen et al, 2018;Pedersen et al, 2018). Our historical demographic changes based on nuclear data indicated that the N e of the southern lineage was strongly affected by the LGM, suggesting rapid demographic declines.…”
Section: Ecological Niche Modellingmentioning
confidence: 89%